WTA Tour: Aquatic therapy for tennis - Heller, L.; Martin, K. (Medicine and Science in Tennis, 2003)
The use of aquatic therapy in professional tennis players' training routines can help them improve their performance on the court, minimize their risk of injury and speed their recovery and rehabilitation from injury. Combining the properties and advantages of water with therapeutic exercise, aquatic therapy is a powerful adjunct to traditional tennis training, injury rehabilitation programs and recovery strategies. The benefits of the aquatic therapy are shown and tips for aquatic therapy routines for tennis players are given.